Above-ground dendromass of sprouted black locust energy plantations: a case study - Keserü, Zs.; Csiha, I.; Bakti, B.; Rédei, K. (International Journal of Horticultural Science, 2017)
Black locust (Robinia pseudoacacia L.) can be considered as one of the most suitable tree species for establishing energy plantations due to its favourable growing characteristics such as vigorous growing potential in the juvenile phase, excellent coppicing ability, a relatively high resistance to pests. Based on national and international test results the mean annual increment of oven-dry weight of energy plantations regenerated by coppicing generally exceeds the first cycle plantations established by seedlings.